A CASE STUDY OF FORMATIVE ASSESSMENT IN A CHINESE HIGH SCHOOL - Tang, Ying (Universitas Pendidikan Indonesia, 2013)
Abstract: Nowadays in China, high school assessment is based solely on academic examination scores, which take the place of well-rounded assessments that should be given to students. The present assessment ignores the differences among individuals and goes against a people-oriented spirit; thus, it is not scientific. This one-sided assessment has caused many negative effects on students and society, and it is not beneficial to students’ well-being. The author performed a study on a formative assessment method using a Portfolio for keeping a record of English learning while growing up to change the present situation of students being tired of study due to low scores. The assessment allows students to understand that their low scores are not because they lack a gift for learning languages, but because they themselves think they lack the ability to learn a foreign language, which leads to their unwillingness to learn English (Ames 1992; Vispoel Austin 1995). The research examines 122 year-11 senior middle school students’ views of the formative assessment method and their improvement in examination scores through the assessment over a period of one to two years. Qualitative and quantitative data were gathered via a questionnaire and interviews. All the data show and prove that the students who have been assessed using formative assessment enjoy going to school and have made more progress than those assessed using summative assessment. This assessment has been warmly welcomed by students, whether they are at a higher or a lower English level.